A case study on the restoration of a three-story historical structure based on field tests, laboratory tests and finite element analyses. (October 2022) - Cakir, Ferit; Kucuk, Sebahattin
Abstract: Masonry buildings have been vulnerable structures to earthquakes due to the brittle nature of the materials used in their construction. Due to strong ground motions, the majority of masonry buildings built in seismic zones are damaged or collapsed. The performance-based evaluation of these structures must be conducted to improve their seismic performance. In this approach, the main goal is to determine structural damage, evaluate the condition of the building based on the results and decide on restoration techniques and materials. In this study, a performance-based evaluation was conducted on a three-story masonry building that was constructed in 1912, and the building was restored in response to the results. In this study, Performance Evaluation Studies are examined under four main steps: (1) Preliminary Evaluation, (2) Damage Survey Studies, (3) Detailed Evaluation Studies and (4) Restoration Implementations.